Penetrance of marked cognitive impairment in older male carriers of the FMR1 gene premutation. Issue 12 (18th June 2009) - Sévin, M; Kutalik, Z; Bergman, S; Vercelletto, M; Renou, P; Lamy, E; Vingerhoets, F J; Di Virgilio, G; Boisseau, P; Bezieau, S; Pasquier, L; Rival, J-M; et al.
Abstract : Background: Male carriers of the FMR1 premutation are at risk of developing the fragile X–associated tremor/ataxia syndrome (FXTAS), a newly recognised and largely under-diagnosed late onset neurodegenerative disorder. Patients affected with FXTAS primarily present with cerebellar ataxia and intention tremor. Cognitive decline has also been associated with the premutation, but the lack of data on its penetrance is a growing concern for clinicians who provide genetic counselling. Methods: The Mattis Dementia Rating Scale (MDRS) was administered in a double blind fashion to 74 men aged 50 years or more recruited from fragile X families (35 premutation carriers and 39 intrafamilial controls) regardless of their clinical manifestation. Based on previous publications, marked cognitive impairment was defined by a score ⩽123 on the MDRS. Results: Both logistic and survival models confirmed that in addition to age and education level, premutation size plays a significant (p<0.01 and p<0.03 for logistic and survival model, respectively) role in cognitive impairment. The estimated penetrance of marked cognitive impairment in our sample (adjusted for the mean age 63.4 years and mean education level 9.7 years) for midsize/large (70–200 CGG) and small (55–69 CGG) premutation alleles was 33.3% (relative risk (RR) 6.5; p = 0.01) and 5.9% (RR 1.15; p = 0.9) respectively. Penetrance in the control group was 5.1%. Conclusions: Male carriers of midsize to large premutation alleles had a sixfold increased risk of developing cognitive decline and the risk increases with allele size. In addition, it was observed that cognitive impairment may precede motor symptoms. These data provide guidance for genetic counselling although larger samples are required to refine these estimates.